PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE DAN KOMPOSISI KOMISARIS INDEPENDEN TERHADAP EARNING MANAGEMENT ( Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2007-2009) - Hani Sri Mulyani (MAKSI, 2014)
This study has purpose to get empirical evidence about effect of company size,profitability, financial leverage and independent commissioners’s proportion to EarningManagement. Company size is measured by total assets companies, profitability measuredusing return on assets/investment (ROA/ROI), financial leverage measured with ratio of debtproportion from total asset of company and mecanism of corporate governance produced byindependent commissioners’s proportion measured with percent of account independentcommissioners’s proportion devided by total commissioners’s memberEarning Management is measured with index eckel. Population of this study is 149manufactures wich are registered in Indonesia Stock Exchange 2007 – 2009. The data ofstudy is found from report of manufactures finance on periode 2007 – 2009. Based onsampling purposive method, sample that is found is 112 companies. Hypotesis in this study istested by using multi regression analysis.Based on the result shows that profitability have a positive and significance relationon the earning management. However company size, financial leverage and independentcommissioners’s proportion have not anysignificance on the earning managementKey words: Corporate Governance, Company size, profitability, financial leverage,earning mangement.I. PENDAHULUA